A new species of the genus Eucibdelus Kraatz, 1859 (Coleoptera: Staphylinidae: Staphylininae) from Yunnan, China - He, Liang; Schillhammer, Harald; Cai, Yanpeng; Li, Xiaoyan (Zootaxa, 2021)
Eucibdelus flavipennis sp. nov. from Yunnan Province, China is described. Line drawings and color illustrations of adult structures and genitalia of the new species are given. The former subgeneric division is shortly discussed.